2021
DOI: 10.1002/jbm.b.34794
|View full text |Cite
|
Sign up to set email alerts
|

The role of surface oxide thickness and structure on the corrosion and nickel elution behavior of nitinol biomedical implants

Abstract: Biocompatibility is an important factor for metallic medical device implants, and corrosion resistance of implantable alloys is one aspect of biocompatibility. Corrosion behavior of nitinol is strongly dependent upon the nature of the surface oxide, which forms during processing. The surface oxide is comprised of a mixture of titanium and nickel oxides, and subsequent thermal exposure (e.g., during shape setting) and surface removal (e.g., electropolishing, mechanical polishing, etching, etc.) influence its st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 19 publications
3
12
0
Order By: Relevance
“…Similar results were observed in several other studies as well. 23,34,46 For instance, Rosenbloom et al 23 reported the E b for EP NiTi samples as ~950 mV whereas the E b for MP NiTi samples was only ~245 mV. Similarly, Thierry et al 34 reported the E b for EP NiTi samples as ~1000 mV with no trace of localized corrosion whereas the E b for MP NiTi samples was ~530 mV (Table 1).…”
Section: Polishing Of Nitimentioning
confidence: 97%
See 3 more Smart Citations
“…Similar results were observed in several other studies as well. 23,34,46 For instance, Rosenbloom et al 23 reported the E b for EP NiTi samples as ~950 mV whereas the E b for MP NiTi samples was only ~245 mV. Similarly, Thierry et al 34 reported the E b for EP NiTi samples as ~1000 mV with no trace of localized corrosion whereas the E b for MP NiTi samples was ~530 mV (Table 1).…”
Section: Polishing Of Nitimentioning
confidence: 97%
“…16,19,20,22 The uniformity of the oxide layer across the entire material surface with respect to thickness and chemical composition is crucial as it determines the efficacy of finishing steps involved. 16,20,23 The stability of the oxide layer is also important since a thick oxide layer can undergo mechanical defects and break whereas a thin oxide layer can be stable and well protective. 20,24,25 There has been a lot of research done to improve the properties of surface oxide with a primary focus on how to prevent the release of nickel ions from NiTi.…”
Section: Surface Finishingmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, many scholars are committed to the application of this technology to prevent atrial fibrillation thromboembolism, and great progress has been made [6][7][8]. Nitinol is a kind of shape memory alloy with excellent characteristics of wear resistance, corrosion resistance, high damping and super elasticity, which is widely used in medical devices [9][10][11]. Therefore, LAA occluder is usually made of nitinol.…”
Section: Introductionmentioning
confidence: 99%